Development of Earthquake Mitigation E-Book for Disability Student - Sayekti, Ika Candra; Susilawati, Siti Azizah; Pramudita, Dias Azis; Johan, Agnes Erni; Yanto, Bambang Tri; Ningsih, Sepfiana Dari; Ismail, Adik; Rosyada, Aulia Qisthi; Tama, Ifan Destya Adi (International Journal of Learning Reformation in Elementary Education, 2024)
This study aims to describe the development of an ebook on earthquake disaster mitigation, analyze the feasibility level of an ebook on earthquake disaster mitigation, and analyze the practicality of an ebook on earthquake disaster mitigation. This development research (RnD) study uses the ADDIE development model. Teachers and students from Klaten Regency's elementary school served as research subjects. The information was gathered using a questionnaire technique. Quantitative data include feasibility and practicality validation values, which refer to a five-interval Likert scale. The data analysis technique uses quantitative descriptive methods to validate feasibility and practicality. Test the validity of the data using member checks. This study shows that the E-book Earthquake Disaster Mitigation, the Canva website designing its ebook, and the software Flip PDF Professional convert PDF into links. Through the assessments of material and media experts, the ebook obtained an average feasibility score of 90% for material experts who showed "very feasible." Meanwhile, media experts received an average score of 93.1%, indicating "very feasible based on the material, presentation, language, and graphics previously analyzed, " so the ebook is suitable. The ebook received an average practice score of 94.7% in a practitioner's test assessment of thirteen representatives of special education teachers from Klaten Regency, indicating a "very practical" result. The e-development books are tailored to the previously identified needs, making them appropriate for children with special needs.